Efficiency and thoroughness trade-offs in high-volume organisational routines: an ethnographic study of prescribing safety in primary care. Issue 3 (9th November 2017) - Grant, Suzanne; Guthrie, Bruce
Abstract : Background: Prescribing is a high-volume primary care routine where both speed and attention to detail are required. One approach to examining how organisations approach quality and safety in the face of high workloads is Hollnagel's Efficiency and Thoroughness Trade-Off (ETTO). Hollnagel argues that safety is aligned with thoroughness and that a choice is required between efficiency and thoroughness as it is not usually possible to maximise both. This study aimed to ethnographically examine the efficiency and thoroughness trade-offs made by different UK general practices in the achievement of prescribing safety. Methods: Non-participant observation was conducted of prescribing routines across eight purposively sampled UK general practices. Sixty-two semistructured interviews were also conducted with key practice staff alongside the analysis of relevant practice documents. Results: The eight practices in this study adopted different context-specific approaches to safely handling prescription requests by variably prioritising speed of processing by receptionists (efficiency) or general practitioner (GP) clinical judgement (thoroughness). While it was not possible to maximise both at the same time, practices situated themselves at various points on an efficiency-thoroughness spectrum where one approach was prioritised at particular stages of the routine. Both approaches carried strengths and risks, with thoroughness-focused approaches considered safer but more challenging to implement in practice due to GP workload issues. Most practices adopting efficiency-focused approaches did so out of necessity as a result of their high workload due to their patient population (eg, older, socioeconomically deprived). Conclusions: Hollnagel's ETTO presents a useful way for healthcare organisations to optimise their own high-volume processes through reflection on where they currently prioritise efficiency and thoroughness, the stages that are particularly risky and improved ways of balancing competing priorities.